UPAYA MENINGKATKAN KINERJA PEMASARAN MELALUI ORIENTASI PASAR DAN ORIENTASI KEWIRAUSAHAAN DENGAN INOVASI SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Usaha Mikro Kecil dan Menengah Kota Semarang) - Mulyaniida, Ida Tri; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2015)
Micro, Small and Medium Enterprises (MSMEs) have an important role for the growth of the national economy. In the first quarter of 2014, the number of MSMEs in Central Java increased, reaching 53.951 business units. However, in line with the increasing number of MSMEs and increasing turnover generated by SMEs in Central Java until 2013, when analyzed the average turnover per MSMEs by dividing turnover per year divided by the number of SMEs, it is known that the average turnover per MSMEs in Central Java in 2013 actually decreased, which decreased by 0.0102 billion from the year 2012. The purpose of this research was to determine the factors that can improve the marketing performance of MSMEs. Empirical studies conducted in this research is on Micro, Small and Medium Enterprises (MSMEs) of Semarang City. The reason is because Semarang is Capital City of Central Java and MSMEs of Semarang contribute most to the GDP of Central Java province.      This study uses four variables: Market Orientation, Entrepreneurship Orientation, Innovation and Marketing Performance. Research hypothesis testing using the data of 120 respondents MSMEs in Semarang City. The analysis technique used in this research is Structural Equation Model (SEM) of 21.0 AMOS program.            The research proves that in order to improve marketing performance on MSMEs can be via 4 process. However, the most influential on the increase marketing performance in MSMEs is to innovate on products that are supported by market-oriented.